2013
DOI: 10.4028/www.scientific.net/msf.738-739.82
|View full text |Cite
|
Sign up to set email alerts
|

Tension - Compression Asymmetry in Co<sub>49</sub>Ni<sub>21</sub>Ga<sub>30</sub> High-Temperature Shape Memory Alloy Single Crystals

Abstract: This paper reports on the tension-compression asymmetry of [001]-oriented Co49Ni21Ga30 single crystals at elevated temperatures. Maximum strains of -4.8 % and 8.6 % in compression and tension, respectively, were found. A linear Clausius-Clapeyron relationship was observed for both stress-states where the smaller slope in tension resulted in a significant increase of the phase transformation temperatures with stress, which reached 180 °C under a constant stress level of 150 MPa. In addition, the material demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…5). At the same time tensile loads favor single martensite variants [23], which is in good agreement with the current results for the evolution of permanent strain as well as for stress hysteresis (Figs. 4, 5).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…5). At the same time tensile loads favor single martensite variants [23], which is in good agreement with the current results for the evolution of permanent strain as well as for stress hysteresis (Figs. 4, 5).…”
Section: Discussionsupporting
confidence: 92%
“…The maximum temperature for PE has been reported to be about 400°C [21]. At the same time formability of the alloy can be adjusted by incorporation of the disordered secondary c-phase (A1) [2,[21][22][23]. Generally, Co-Ni-Ga alloys undergo a martensitic transformation to a tetragonal structure (L1 0 ) from the high-temperature cubic B2-structured austenite [12,14,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Heusler-type Co-Ni-Ga alloy which is subject of the current study was initially developed to exploit magnetic shape memory effects [12]. However, Co-Ni-Ga has proven good pseudoelastic behaviour at elevated temperatures up to 400 °C making it attractive for HT-SMA applications [9,10,13,[14][15][16][17][18][19]. Moreover, in a very recent study it was shown that Co-Ni-Ga can be qualified for HT actuation [19].…”
Section: ____________________________________________________________mentioning
confidence: 95%
“…Using the single crystals of Co 49 Ni 21 Ga 30 alloy with orientation [001], it was shown that a plot of superelasticity obtained during tension and compression of single crystals have a different view (have asymmetry) [52]. The value of SE is also different.…”
Section: Superelasticitymentioning
confidence: 99%